Transfer of genetic information within a colony of Haemophilus influenzae. - Stuy, J H (1985)
Different Haemophilus cultures were mixed and then spotted onto an agar plate. These mixed colonies were incubated at 37 degrees C and then scored for the presence of recombinants. It was found that conjugative plasmids transferred very efficiently and quickly under these conditions, but only between cells of the same species. Four small plasmids did not transfer at all, nor were they mobilized by the two conjugative plasmids studied. Chromosomal markers transferred very inefficiently. The evidence favored transfer by genetic transformation rather than by conjugation. When mixed cultures were inoculated into broth and then incubated, the transfer of conjugative plasmids was not observed. Transfer of chromosomal markers occurred only when the media used contained Eugonbroth in addition to brain heart infusion, and even then it was very inefficient. The addition of DNase completely eliminated such transfers. This and other evidence indicate that in cell suspensions, chromosomal marker transfer also occurs through transformation. A corrected map of several genetic markers is presented.